Molecular dissection method using trans-splicing to designed spliced leader sequences, genes, and constructs thereof (2004)
The presently disclosed subject matter generally relates to a method for detectably labeling ribonucleic acid molecules expressed in cells of interest. Also provided are methods for isolating ribonucleic acid molecules derived from genes that are expressed in cells of interest.